Peran Persekutuan Wanita Kristen dalam Pemulihan Kerohanian Penyintas Post Traumatic Stress Disorder (PTSD) - Yoelianna Herawaty Onggy; Stella Leoni; Linda Arih Ersada (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study thoroughly explores the role of Christian women’s fellowship as a locus of spiritual recovery for survivors of Post-Traumatic Stress Disorder (PTSD). The research was conducted through a library study of scholarly literature published in the past decade on faith-based community support, religious coping, and trauma-informed ministry. Thematic analysis indicates that women’s fellowship can provide a safe and inclusive recovery environment, facilitate faith reconstruction through positive religious coping and trauma-sensitive practices, and bridge spiritual care with professional mental health services. The novelty of this research lies in integrating recent findings from the psychology of religion with pastoral theology principles to develop a theoretical-practical framework adaptable to church contexts. The practical implications include implementing trauma-informed ministry standards, designing adaptive spiritual curricula, training facilitators, and conducting continuous evaluations. Therefore, Christian women’s fellowship has the potential to strengthen the church’s capacity as a holistic, safe, and resilient recovery community for PTSD survivors.